Estudo epidemiológico de tumores estromais gastrointestinais e outros sarcomas que afetam o intestino de cães - Costa, Marina Laudares (2022)
The gastrointestinal system is composed of a variety of cells, which can result in the development of different neoplasms, with different clinical signs and similar histomorphological characteristics, being often confused with other comorbidities, making diagnosis and treatment difficult. Given the morphological similarity between gastrointestinal stromal tumors and other sarcomas of the intestine of dogs, combined with the scarcity of studies proving the true frequency of these neoplasms, the aim of the present study was to carry out an epidemiological survey of suspected cases of gastrointestinal stromal tumors in dogs, diagnosed by histopathology and confirmed by immunohistochemistry, from the Veterinary Clinical Analysis Laboratory - VetPat (Campinas, SP), from June 2014 to December 2020, in addition to associating them with the patients' review (race, sex and age), tumor location and invasion, mitotic index and immunohistochemical markers used. The results obtained were expressed descriptively and as a percentage. A total of 217 histopathological reports were obtained and only 36 animals were included in the study that were definitively diagnosed by immunohistochemistry. The main breeds diagnosed in the gastrointestinal stromal tumors were mixed breed dogs, Dachshund, Poodle and Golden Retriever, represented mainly by elderly women, while in the other sarcomas the main affected breeds were mixed breeds and Dachshund, being males and women equally affected. The cecal region and the small intestine were the most common intestinal culminations, with tumor invasion of the intestinal layers in 31 animals and ulceration in six of them. The number of mitotic figures ranged from three to 17 figures, in 16 of 36 tumors taken. Gastrointestinal stromal tumors frequently expressed markers such as CD117 and DOG-1, unlike other intestinal sarcomas, being fundamental immunohistochemistry for determining the diagnoses. KEYWORDS: canine; CD117; DOG-1; GIST; intestine; neoplasm.